Incorporating coopetition into the entrepreneurial marketing literature: Directions for future research. Issue 1 (8th July 2019) - Crick, James M.
Abstract : Purpose: The purpose of this paper is to extend the entrepreneurial marketing literature to account for coopetition (the interplay between cooperation and competition). This paper is also designed to highlight the research gaps surrounding coopetition, so that academics, working at the marketing/entrepreneurship interface, can undertake more investigations linked with this topic. Design/methodology/approach: The entrepreneurial marketing literature was reviewed to develop a conceptual framework, guided by three research propositions, examining the antecedents and consequences of coopetition, as well as the boundaries of the coopetition–organisational performance relationship. Findings: Coopetition activities are driven by an organisation-wide coopetition-oriented mindset – the degree to which managers and employees believe in the importance of cooperating with competitors. Also, coopetition can help entrepreneurs access new resources and capabilities from their competitors; however, "too much" coopetition can lead to tensions between such rival firms. Additionally, it is proposed that the relationship between coopetition activities and organisational performance is moderated by competitive intensity (a facet of the competitive business environment). That is, with higher levels of competitive intensity, entrepreneurs are less likely to improve their performance from coopetition activities. That is, the competitive business environment can affect the delicate balance between the forces of cooperativeness and competitiveness. Originality/value: Entrepreneurial marketing research has concentrated on individualistic perspectives concerning how entrepreneurs operate their businesses. In this viewpoint, the competitive assumptions of the marketing/entrepreneurship interface are extended to account for coopetition. This paper also outlines the areas within the coopetition literature that entrepreneurial marketing scholars should appreciate. Specifically, entrepreneurial marketing scholars are recommended to examine the antecedents and consequences of coopetition, coupled with the moderating role of competitive intensity (a facet of the competitive business environment) in the coopetition–organisational performance relationship. This paper ends with a recommended methodology for academics to test the conceptual framework in future empirical research.